Maxillary Sinus Membrane Elevation With Simultaneous Installation of Implants Without the Use of a Graft Material: A Systematic Review. Issue 4 (August 2017) - Starch-Jensen, Thomas; Schou, Søren
Abstract : Objective: To compare implant treatment outcome after maxillary sinus membrane elevation with simultaneous installation of implants with or without the use of graft material applying the lateral window technique. Materials and Methods: MEDLINE/PubMed, Cochrane Library, and Embase search in combination with a hand-search of relevant journals was conducted from January 1, 2004 to January 1, 2016. Results: Thirteen studies fulfilled the inclusion criteria. Survival of suprastructures has not been compared within the same study. Short-term implant survival without graft material varied between 96% and 100% compared to 100% for autogenous bone or bone substitutes. No significant difference in bone gain was reported without graft material compared to autogenous bone. The density of newly formed bone increased significantly during the observation period. Bone density was significantly higher in sinuses augmented with blood clot compared to bone substitute, whereas no significant difference was found when compared to autogenous bone. Noncomparative studies demonstrated high long-term implant survival and new bone formation after sinus membrane elevation without graft material. Conclusions: Sinus membrane elevation without the use of a graft material seems to enhance new bone formation with high implant survival, but long-term comparative studies are missing.